ANALISIS FAKTOR PENDUKUNG DALAM UPAYA PENINGKATAN PELAYANAN PADA PELABUHAN TANJUNG INTAN CILACAP - Kristian Cahyandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2018)
An efficient and well-managed sea transportation system is a very important factor in improving the national economy. Ports in Indonesia, which are considered to be less efficient and not well equipped / managed, are significant factors that increase shipping costs. For example, ships that are involved in domestic trade are mostly from the time of manufacture only to be propped up or waiting inside or outside the port. The Shipping Law of 2008 provides the foundation for a comprehensive system reform in Indonesia. What is striking is that the shipping law removes the government's monopoly on the port sector and reveals the participation of the private sector. This can affect prices that are very needed in the port sector, providing pressure to reduce prices, and accelerate price increases. Operational performance standards have been established as government standards and international standards. In meeting these standards Tanjung Intan Cilacap Port is required to be able to provide good operational performance, therefore there is a need for performance needed to measure performance and projections of future needs. In this study, it was used to determine the specific port for general cargo.